Prognostic Value of CRASH and IMPACT Models for Predicting Mortality and Unfavorable Outcome in Traumatic Brain Injury; a Systematic Review and Meta-Analysis - Zarei, Hamed; Vazirizadeh-Mahabadi, Mohammadhossein; Adel Ramawad, Hamzah; Sarveazad, Arash; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2023)
Introduction: The Corticosteroid Randomization After Significant Head injury (CRASH) and the International Mission for Prognosis and Analysis of Clinical Trials (IMPACT) are two prognostic models frequently used in predicting the outcome of patients with traumatic brain injury. There are ongoing debates about which of the two models has a better prognostic value. This study aims to compare the CRASH and IMPACT in predicting mortality and unfavorable outcome of patients with traumatic brain injury. Method: We performed a literature search using Medline (via PubMed), Embase, Scopus, and Web of Science databases until August 17, 2022. After two independent researchers screened the articles, we included all the original articles comparing the prognostic value of IMPACT and CRASH models in patients with traumatic brain injury. The outcomes evaluated were mortality and unfavorable outcome. The data of the included articles were analyzed using STATA 17.0 statistical program, and we reported an odds ratio (OR) with a 95% confidence interval (95% CI) for comparison. Results: We included the data from 16 studies. The analysis showed that the areas under the curve of the IMPACT core model and CRASH basic model do not differ in predicting the mortality of patients (OR=0.99; p=0.905) and their six-month unfavorable outcome (OR=1.01; p=0.719). Additionally, the CRASH CT model showed no difference from the IMPACT extended (OR=0.98; p=0.507) and IMPACT Lab (OR=1.00; p=0.298) models in predicting the mortality of patients with traumatic brain injury. We also observed similar findings in the six-month unfavorable outcome, showing that the CRASH CT model does not differ from the IMPACT extended (OR=1.00; p=0.990) and IMPACT Lab (OR=1.00; p=0.570) in predicting the unfavorable outcome in head trauma patients. Conclusion: Low to very low level of evidence shows that IMPACT and CRASH models have similar values in predicting mortality and unfavorable outcome in patients with traumatic brain injury. Since the discriminative power of the IMPACT Core and CRASH basic models is not different from the IMPACT extended, IMPACT Lab, and CRASH CT models, it may be possible to only use the core and basic models in examining the prognosis of patients with traumatic injuries to the brain.